2014
DOI: 10.1891/0889-8391.28.4.251
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive-Compulsive Symptoms and Beliefs in Adolescents: A Cross-Sectional Examination of Cognitive Models

Abstract: Cognitive models of obsessive-compulsive disorder (OCD) posit that particular beliefs transform normal intrusions into disturbing obsessions. A wealth of data shows that such beliefs and obsessive-compulsive (OC) symptoms are related in adults. However, there is markedly less information regarding OCD-related beliefs in youth. The purpose of this study was to assess the relation between OCD-related beliefs and OC symptoms in unselected adolescents (ages 13–18 years; N = 159). Findings from questionnaires compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
2
2
0
Order By: Relevance
“…A more recent study, however, found that perfectionism and certainty beliefs in an unselected sample of adolescents were similar to levels found in previous studies of young people with an OCD diagnosis (Coles, Ravid, Franklin, Storch, & Khanna, 2014). Perfectionism beliefs have also been shown to correlate with OC symptoms (Coles et al, 2014; Huan, Rice, & Storch, 2008; Soreni et al, 2014). For instance, Soreni et al (2014) found that perfectionism beliefs were associated with severity of OCD and depressive symptoms in children and adolescents with OCD.…”
Section: Cognitive Processes In Ocdsupporting
confidence: 78%
See 2 more Smart Citations
“…A more recent study, however, found that perfectionism and certainty beliefs in an unselected sample of adolescents were similar to levels found in previous studies of young people with an OCD diagnosis (Coles, Ravid, Franklin, Storch, & Khanna, 2014). Perfectionism beliefs have also been shown to correlate with OC symptoms (Coles et al, 2014; Huan, Rice, & Storch, 2008; Soreni et al, 2014). For instance, Soreni et al (2014) found that perfectionism beliefs were associated with severity of OCD and depressive symptoms in children and adolescents with OCD.…”
Section: Cognitive Processes In Ocdsupporting
confidence: 78%
“…One study found that young people with OCD had significantly higher ratings of perfectionism beliefs (i.e., concern over mistakes) compared to both anxious and non-clinical controls (Libby et al, 2004). A more recent study, however, found that perfectionism and certainty beliefs in an unselected sample of adolescents were similar to levels found in previous studies of young people with an OCD diagnosis (Coles, Ravid, Franklin, Storch, & Khanna, 2014). Perfectionism beliefs have also been shown to correlate with OC symptoms (Coles et al, 2014; Huan, Rice, & Storch, 2008; Soreni et al, 2014).…”
Section: Cognitive Processes In Ocdsupporting
confidence: 78%
See 1 more Smart Citation
“…Evidence from more recent primary studies in large community or clinical samples of adolescents [23][24] supported the cross-sectional association between Perfectionism and Intolerance of Uncertainty and OCD even when controlling for anxiety and depressive symptoms. Other studies found a speci c relation of Perfectionism and Intolerance of Uncertainty with symmetry and ordering symptoms [25]. In a group of adolescents with OCD, very strong correlations between overvalued ideation were reported, a cognitive domain which is similar to the Importance of Thoughts belief, and OCD severity [26].…”
Section: Introductionmentioning
confidence: 94%